Wheelchair velocity of tennis players during propulsion with and without the use of racquets - Goosey-Tolfrey, V. L.; Moss, A. D. (Adapted Physical Activity Quarterly, 2005)
To compare the velocity characteristics of wheelchair propulsion with and without the use of a tennis racquet, eight male wheelchair tennis players performed a series of 20m sprints from a stationary start. The maximum velocities reached on average 4.39 ± 0.74 m/s; however, they were reduced by 0.18 ± 0.06 m/s during the racquet condition. Furthermore, when wheeling under the racquet condition, the velocities achieved during the first three pushes were significantly reduced. The reduction in maximum velocity and relative velocity contributions while holding a tennis racquet may have been due to an ineffective push technique resulting in low effectiveness of force application. The relation of these parameters and trunk stability is discussed.